Some considerations about the past, present and future of Europe (De Rebus Antiquis, 2020)
The aim of this paper is to tour the various places where ancient classical thought has been approached “Europe” as a concept and reality. First, searching in their testimonies it will discuss how they were building and transforming a geographic awareness of the European territorial space. Second, it will outline the way that was structured the “myth” of Europe as a goddess, for then to see how they structured the “idea” of Europe, affirming fundamentally opposed to Asia and consolidating in the association of continent and Christianity in medieval times. Finally, we analyze the concept as a historical reality, to finally to reflect briefly on the situation of European culture and worldview in the twentieth century until today.
Keywords: Europe; geography; myth; idea; history